Correction: Dominant-Negative Effect of a Missense Variant in the TASK-2 (KCNK5) K+ Channel Associated with Balkan Endemic Nephropathy. - Alan P Reed; Giovanna Bucci; Firdaus Abd-Wahab; Stephen J Tucker (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0156456.].